INTERROGANTES Y REFLEXIONES SOBRE IGLESIA VS ESTADO (ITER Humanitas. Revista de Filosofía y Humanidades, 2026)
We proposed a serie aj questions about the relations between the Church and the State, to prevent disagreements. lt is also pretended to make clear the dijferences between laycity and laicism. Catholics are invite to clarify ideas and to avoid false concepts. We wonder if the practice ofÍaith should be considered as a Human Right, and in this case, if the State would be obligated to support it. We en wondering if Religion could be a source ofjuridical arder and recommending to ali the believers to recognize our own failures and to fulfill the civil laws.